Gambaran C-Reactive Protein pada Pasien dengan Diagnosa Demam Typhoid di RSU Hermina Arcamanik - Nadia Sri Oktoria; Agus Sudrajat (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Typhoid fever is an acute systemic disease. This fever is caused by bacteria called salmonella typhi. This type of bacteria commonly lives and is found in the digestive tract. Typhoid fever can usually be transmitted through food or drink, as long as both have been contaminated and exposed to the bacteria whose names have been mentioned previously. C-Reactive Protein is a test that is used to measure the level of C-Reactive in the blood and produced by the liver, then the results of this production are used to respond to inflammation that occurs by releasing it into the bloodstream. The aim of this study was to determine the appearance of C-reactive protein in patients diagnosed with typhoid fever at RSU Hermina Arcamanik. Quantitative descriptive is the method used and applied in this research, while for the approach the researcher used cross-sectional. The sample population is all data on patients positive for typhoid fever, totaling 30 samples of patients who checked CRP and data collection using secondary data. The research results from 30 samples showed high results at the age of 30-40 years as many as 16 (53%) and high results at the age of 41-50 years as many. 5 (17%), while it was based on 10 (33%) men and 13 (43%) on women.